(untitled) (Journal of Hama University, 2022)
Training students during the educational curricula to apply the rubber and emphasizing the mandatory use of it and its adoption as an effective technique to isolate the work field correctly is one of the most important goals of the educational process because of its great impact on clinical practice, so the purpose of this study was to evaluate the installation of the rubber diaphragm in pediatric dental clinics At Damascus University for undergraduate students. 62 students were randomly selected, and photographs of the treated children were made after completing the installation of the rubber barrier for them, and a single observer monitored the errors committed during the installation of the rubber barrier on the solar pictures placed on the computer screen, then the information contained in the Excel table was entered for analysis and retention of the values obtained anonymously by de-identifying the participants. The results of the questionnaire were varied, as the percentage of not tying the clamp with a dental thread was the highest and equal to 98.3%, and the percentage of not using a saliva absorber was 83.87%, which is the second highest percentage, and the percentage of error in covering rubber was 54.8%, while the rest of the errors committed were similar , It is necessary to increase focus and training on the use of rubber diaphragms in university curricula through the educational process and increase guidance and follow-up by supervisors in practical sessions to ensure the optimal application of the rubber diaphragm because this will determine the correct future use of the rubber septum in general clinical practice.